Scattering of Rayleigh Waves by a Trapezoidal Canyon - Haeri, S.; Ghadimi, Behzad; Nikraz, Hamid (Research Publishing Services, 2012)
The response of a typical trapezoidal cross section canyon to Rayleigh waves is reported in this paper. A new approach based on Scaled Boundary Finite Element Method (SBFEM) is used to obtain scattered motion along the canyon. The analysis is performed in time domain. A harmonic excitation is applied to the undamped media and the scattered motion is obtained. The result of the study indicates that the upper parts of the canyon are more critical than the bottom also the side which is closer to the incident wave experiences higher excitation compared to other parts of the canyon.